Research progress in physiological effects of resistant substances of Urtica dioica L. on animal performance and feed conversion - Zhang, Yifan; Zhang, Xin; Zafar, Muhammad Hammad; Zhang, Jinying; Wang, Jiasheng; Yu, Xiang; Liu, Wujun; Wang, Mengzhi (Frontiers in Plant Science, 2023)
Several members of family Urticaceae are mainly found in the temperate and subtropical zones of the Northern Hemisphere and are important medicinal plants. Among them, Urtica dioica L. (Urticaceae) is an annual or perennial herb that has been used for feeding and medicinal purposes since long time and is the most exploited species of Urticaceae. Recently, it has received attention to be used as animal feed, as its fresh leaves fed to animals in moderate, dried, and other forms. This review details the advantages of U. dioica as an alternative feed in terms of germplasm specificity, nutritional composition, and feed application status. Its roots, stems, leaves, and seeds are rich in active ingredients. It has also been found to have anticancer effects through antioxidant action and promotion of apoptosis of cancer cells. In shady conditions, U. dioica is highly adaptable while under stressful conditions of drought; it also reduces light absorption and ensures carbon assimilation through light energy conversion efficiency. Therefore, it can be added to animal diets as a suitable feed to reduce costs and improve economic efficiency. This paper investigates the feasibility of using U. dioica as a feed and systematically presents the progress of research and exploitation of U. dioica.